Micronuclei and sister chromatid exchanges induced by capsaicin in human lymphocytes - Marques, S (2015)
Capsaicin is the main pungent and irritating component of hot peppers (species Capsicum annuum and C. frutescens). Genotoxicity and carcinogenicity studies evaluating capsaicin effects are sparse and contradictory. In this study, we investigated the genotoxicity of capsaicin (10-200 muM) in human peripheral blood lymphocytes using the cytokinesis-block micronucleus (CBMN) assay and the sister chromatid exchange (SCE) assay in the presence or absence of external metabolic activation. Capsaicin induced the formation of micronuclei (MN) in a dose-dependent manner in the cytokinesis-blocked lymphocytes. This increase was more evident in the absence of metabolic activation, with a maximum of 3.4-fold increase above the background. Some inter-individual variability was observed. The results for the SCE assay also show that capsaicin is genotoxic and in this case with a more homogenous response among donors. This end-point, however, has proven to be less sensitive than the CBMN assay for capsaicin. (C) 2002 Elsevier Science B.V. All rights reserved.